Construction of high-density bin genetic map and QTL mapping of fruit aroma in longan (Dimocarpus longan Lour.) - Hu, Wenshun; Zhang, Qing; Deng, Chaojun; Xu, Qizhi; Jiang, Jimou; Chen, Xiuping; Li, Jianguo; Zhang, Jisen; Zheng, Shaoquan (Frontiers in Plant Science, 2025)
Aroma is a crucial factor influencing the flavor quality and economic value of longan fruits. This study employed a mapping population consisting of 98 F1 progeny of ‘Shixia × Xiangcui’ (exhibiting broad segregation in fruit aroma trait) and their parents. We performed the SNP genotyping through whole-genome resequencing to construct a high-density linkage map, followed by QTL mapping and candidate gene screening for aroma trait. We obtained a total of 554.9 Gbp of sequencing data, with an average depth of approximately 15× for the parents and 12× for the progeny. Three types of SNP markers (lm×ll, nn×np, and hk×hk) were developed, totaling 317 877. After merging with a 100 kb sliding window, 6 134 Bin markers were generated. A first high-density Bin map was constructed, comprising 15 linkage groups with 3 517 Bin markers (containing 264 385 SNPs), covering a total map length of 1 666.79 cM. The average marker interval was 0.48 cM, with 99.18% of gaps being less than 5 cM. Collinearity analysis confirmed the high quality of the map. Fifty-six QTLs were mapped for 9 aroma-related traits, including (E)-2-hexenal, ethyl acetate, ethyl butyrate, ethyl crotonate, (E)-2-hexenoate, ethanol, linalool, ocimene, and total ester content. These QTLs explained 19.8%–51.0% of the phenotypic variation rates and were distributed across 11 linkage groups, with two QTL-rich regions on LG7 and LG8. Seven pleiotropic QTLs were detected. By analyzing the expression patterns of 1 535 annotated genes within the mapped intervals, six candidate genes potentially regulating the synthesis of ester characteristic aroma compounds were identified: aldo-keto reductase AKRs, acetolactate synthase small subunit ALS2, ACC oxidase ACO1-1, and transcription factors bHLH122, AGL103, and bZip1. This work provides novel insights into the fruit aroma formation, and facilitates breeding efforts to improve quality in longan and potentially other fruit crops.